Effects of a peer co-facilitated educational programme for parents of children with ADHD: a feasibility randomised controlled trial protocol - Ingunn Mundal; Rolf W Gråwe; Hege Hafstad; Carlos De las Cuevas; Mariela Loreto Lara-Cabrera (BMJ Open)
Introduction Significant numbers of children with attention deficit hyperactivity disorder (ADHD) display problems that cause multiple disabilities, deficits and handicaps that interfere with social relationships, development and school achievement. They may have multiple problems, which strain family dynamics and influence the child’s treatment. Parent activation, described as parents’ knowledge, skills and confidence in dealing with their child’s health and healthcare, has been shown to be an important factor in improving health outcomes. Research suggests that parents need edification to learn skills crucial to the treatment and management of their children’s healthcare. Promoting positive parenting techniques may reduce negative parenting factors in families. This study aims to assess the acceptability, feasibility and estimated sample size of a randomised controlled trial (RCT) comparing an ADHD peer co-led educational programme added to treatment as usual (TAU).Methods and analysis Using a randomised waitlist controlled trial, parents of children aged 6–12 years newly diagnosed with ADHD, and referred to a child mental health outpatient clinic in Mid-Norway, will receive TAU concomitant with a peer co-facilitated parental engagement educational programme (n=25). Parents in the control group will receive TAU, and the educational programme treatment within a waitlist period of 3–6 months (n=25). Parent activation, satisfaction, well-being, quality of life and treatment adherence, will be assessed at baseline (T0), 2 weeks (T1) pre–post intervention (T2, T3) and at 3 months follow-up (T4). Shared decision making, parents preferred role in health-related decisions and involvement, parent-reported symptoms of ADHD and child’s overall level of functioning will be assessed at T0 and T4. Such data will be used to calculate the required sample size for a full-scale RCT.Ethics and dissemination Approval was obtained from the Regional Committee for Medicine and Health Research Ethics in Mid-Norway (ref: 2018/1196). The findings of this study are expected to provide valuable knowledge about how to optimise family education and management of ADHD and will be disseminated through presentations at conferences and publication in peer-reviewed journals.Trial registration number NCT04010851.